Manufacturing data for the implementation of data-driven remanufacturing for the rechargeable energy storage system in electric vehicles - Okorie, Okechukwu; Salonitis, Konstantinos; Charnley, Fiona; Moreno, Maria; Turner, Christopher J.; Tiwari, Ashutosh (Springer, 2019)
Manufacturing industries are experiencing a data-driven paradigm shift that is changing how technical operations are run and changing present business models. Leveraging on manufacturing data from industries and digital intelligence platforms have become important in creating new forms of value. While extending the life of a product through the circular economy 3 R’s of reuse, re-manufacturing and recycling remains a technical and resource challenge for practitioners, optimizing the increasing forms and volumes of data presents a complementary and necessary challenge to the circular economy. This research aims to explore how the manufacturing data can inform remanufacturing parameters for implementing remanufacturing on the Rechargeable Energy Storage System.
Keywords: Remanufacture; Rechargeable energy storage system; Circular approach; Decision-making Internet of Things